PENGARUH KOMPETENSI KARYAWAN, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DINAS PENANAMAN MODAL DAN PERIZINAN TERPADU SATU PINTU KABUPATEN DHARMASRAYA - Mayroza Wiska; Eka Ermawati; Metri Ronaldi (MANAJEMEN DEWANTARA, 2022)
The One Stop Integrated Licensing Investment Office (DPMPTSP) Dharmasraya is one of the agencies whose functions are to prepare investment plans, review the development of the investment climate, carry out investment promotions, and provide investment licensing services. This study wants to see how far the influence of employee competence, work environment and work motivation on employee performance. This study was conducted to determine and analyze what kind of influence is caused by the influence of employee competence, work environment and work motivation on employee performance. The purpose of this study was to determine and analyze "the influence of employee competence, work environment and work motivation on employee performance". This research uses quantitative methods, by distributing questionnaires, the respondents who are used as samples are as many as 50 respondents. The results of this study indicate that based on the results of the F test, it is found that employee competence (x1), work environment (x2) and employee motivation (x3) have a simultaneous significant effect on employee performance (y). value of 34.227 can be seen this test is carried out by comparing the F-count value with the F-table because the F-count value is greater than the F-table value (34.227 > 3.20). The F-count value is 34.227 with a significant level (0.000<0.005). so that jointly employee competence, work environment and work motivation have a simultaneous effect on employee performance. Then it can be obtained that H0 is rejected, H4 is accepted, it means that employee competence, work environment and work motivation have a positive and significant effect on employee performance. The value of R square of employee performance (Y) is 0.691 or 69.1% while the value of Adjusted R Square (coefficient of determination) is 0.691 or 69.1% while the remaining 30.9% is explained by other variables not examined in this study.